2010
DOI: 10.1161/strokeaha.110.581686
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Model Characterizing Features of Vascular Dementia With Hippocampal Atrophy

Abstract: Background and Purpose-We have previously described effects of chronic cerebral hypoperfusion in mice with bilateral common carotid artery stenosis (BCAS) using microcoils for 30 days. These mice specifically exhibit working memory deficits attributable to frontal-subcortical circuit damage without apparent gray matter changes, indicating similarities with subcortical ischemic vascular dementia. However, as subcortical ischemic vascular dementia progresses over time, the longer-term effects that characterize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
188
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 177 publications
(210 citation statements)
references
References 29 publications
18
188
4
Order By: Relevance
“…Another possible explanation for the discrepancy could be that FADD and/or hypoperfusion is influencing other aspects of behavior not related to spatial memory, such as motivation, attention, mobility, or anxiety in the Ung−/−.We found that there was decreased anxiety in the hypoperfused Ung−/− mice when compared to shams. Indeed, decreased anxiety has been reported following hypoperfusion by other groups [36,58], though, it has been suggested that hypoperfusion may simply be increasing activity levels, rather than anxiety, by another group that observed hypoperfused mice made more entries into both the open and closed arms of the elevated plus maze [59]. We did not observe differences in activity between groups during any of the tests.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Another possible explanation for the discrepancy could be that FADD and/or hypoperfusion is influencing other aspects of behavior not related to spatial memory, such as motivation, attention, mobility, or anxiety in the Ung−/−.We found that there was decreased anxiety in the hypoperfused Ung−/− mice when compared to shams. Indeed, decreased anxiety has been reported following hypoperfusion by other groups [36,58], though, it has been suggested that hypoperfusion may simply be increasing activity levels, rather than anxiety, by another group that observed hypoperfused mice made more entries into both the open and closed arms of the elevated plus maze [59]. We did not observe differences in activity between groups during any of the tests.…”
Section: Discussioncontrasting
confidence: 48%
“…At any rate, deficits in the MWM were not surprising during this study, as performance in this task is dependent on hippocampal function. The hippocampus has consistently been described as being affected by hypoperfusion [36,58]. Furthermore, folic acid deficiency results in hippocampal neurodegeneration [33,60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, telmisartan may have restored frontal-subcortical circuitry function, which is also associated with spatial working memory. 8,14 However, hippocampal changes appear at 3 months post-BCAS 15 ; it would therefore be of interest to extend the observation period to investigate effect of telmisartan on the gray matter in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…The BCAS model is a model of chronic cerebral hypoperfusion induced by placement of microcoils around both carotid arteries [21]. In this model a reduced CBF, activation of microglia and astroglia, white matter lesions, grey matter changes, hippocampal atrophy and micro-infarcts have been described [21][22][23][24][25]. TAC, the ligation of the aortic arch between the carotids, is a mouse model of chronic heart failure leading to a reduced ejection fraction [26,27].…”
mentioning
confidence: 99%